ENHANCED SYNTHESIS OF NiO NANO FILM THROUGH SOL-GEL DIP COATING METHOD: INVESTIGATION THE IMPACT OF LASER IRRADIATION - Muhsen Esmael, Mahira (Science Journal of University of Zakho, 2024)
The sol-gel synthesis technique was used to fabricate NiO nanofilms, and the process of dip coating aided by laser irradiation was used to form thin layers on silicon and glass bases at room temperature. By using lasers, a novelty was introduced to the technique that differs from another research. The thin layer was exposed to laser illumination (530 nm, 0.1, 1, 10 W) prior to heating during the deposition process. The main objective is to investigate the properties of thin layers further upon their formation as nanostructures using dip coating under different intensities of green laser light. We characterized the chemical bonding structure and surface morphology with the help of FTIR spectroscopy and SEM. Diffraction X-ray and UV spectroscopy were applied to evaluate the optical and structural characteristics of the films. Surface chemical composition was analyzed using EDS. The FTIR study demonstrated the existence of many exterior groups functional in the NiO nanofilms. NiO nanoparticles showed blue shifts in their infrared absorption band regarding the bulk NiO. The increase in NiOx film's optical bandgap was observed with the rise of laser irradiation intensity; values were found in the range of 3.5–4.01 eV. From the morphological analysis, the nanocrystalline grains in the films are uniformly covered. Through EDS testing, the composition of oxygen and nickel was confirmed. XRD measurements confirmed that during the synthesis process, cubic NiO nanoparticles were obtained. The effects of different power levels of laser irradiation on the films were discussed. According to the findings, High-irradiation laser in dip coating increased synthesis in the deposited films improved optical and structural characteristics adjusted for exact technological applications.